2016
DOI: 10.1111/bjet.12424
|View full text |Cite
|
Sign up to set email alerts
|

Integrating socio‐cultural contexts and location‐based systems for ubiquitous language learning in museums: A state of the art review of 2009–2014

Abstract: Context‐dependent learning systems are now becoming more common in museums, as most students are equipped with mobile devices. As there has been little research into context‐aware mobile applications in museums, the present study aims to investigate ubiquitous language learning in socio‐cultural contexts, as well as recent trends in using location‐based systems. Therefore, the following three issues are reviewed in related articles published between 2009 and 2014: system usefulness, activity usefulness and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 46 publications
0
53
0
1
Order By: Relevance
“…Immediacy allows learners to access learning materials instantly, while interactivity refers to interaction that occurs not only among learners and learners or teachers, but also between learners and the learning devices themselves. Finally, situations means that with the assistance of mobile devices and sensing tools, learning can become pervasive in daily life in an authentic and natural way, and thus the learners eventually become unconscious of the learning processes that are occurring (Liu, Kuo, Shi, & Chen, ; Wang et al, ).…”
Section: Background Significance and Objectives Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Immediacy allows learners to access learning materials instantly, while interactivity refers to interaction that occurs not only among learners and learners or teachers, but also between learners and the learning devices themselves. Finally, situations means that with the assistance of mobile devices and sensing tools, learning can become pervasive in daily life in an authentic and natural way, and thus the learners eventually become unconscious of the learning processes that are occurring (Liu, Kuo, Shi, & Chen, ; Wang et al, ).…”
Section: Background Significance and Objectives Of The Studymentioning
confidence: 99%
“…Ubiquitous computing sensing technology has considerable potential for application in u‐learning, which aims to provide users with the right content at the right time and in the right place (Liu et al, ; Wang et al, ). Many studies (eg, Liu et al, ) have aimed to help learners to combine the context they are in with specific learning content to make learning more authentic and meaningful.…”
Section: Background Significance and Objectives Of The Studymentioning
confidence: 99%
“…Active learning can be promoted using 'playful', fun activities designed in language learning apps that take the students out of the classrooms into museums and other socio-cultural contexts for their learning (Wang et al, 2017). Additionally, the new knowledge that the participants mostly prefer using Google Translate and online dictionaries for language learning suggest that mobile apps designers should consider the simple functionality of these apps and intentionality of the users into their future designs.…”
Section: Resultsmentioning
confidence: 99%
“…There were mobile learning applications on vocabulary and grammar lessons (Thornton and Houser, 2005), the use of text messages to learn Italian outside the classroom (Levy and Kennedy, 2005;Kennedy et al, 2008), the development of 'short (from 30 seconds to 10 minutes) learning modules' to cater to the 'highly fragmented' attention of m-learners (Trifanova andRonchetti, 2003, p. 1796) and more active language learning in museums (Wang et al, 2017). Viberg and Grönlund, (2012) reviewed MALL research (2007 in the explicit area of second language acquisition and found that mobile technology could enhance learners' second language acquisition.…”
Section: Literature Review: Mobile Assisted Language Learningmentioning
confidence: 99%
See 1 more Smart Citation